A Method for Examining the Equating of Psychometric Scales and Tests: An Application Using Dementia Screening Test Batteries. (February 2020) - Dowling, N. Maritza; Raykov, Tenko; Marcoulides, George A.
Equating of psychometric scales and tests is frequently required and conducted in educational, behavioral, and clinical research. Construct comparability or equivalence between measuring instruments is a necessary condition for making decisions about linking and equating resulting scores. This article is concerned with a widely applicable method for examining if two scales or tests cannot be equated. A latent variable modeling method is discussed that can be used to evaluate whether the tests or parts thereof measure latent constructs that are distinct from each other. The approach can be routinely used before an equating procedure is undertaken, in order to assess whether equating could be meaningfully carried out to begin with. The procedure is readily applicable in empirical research using popular software. The method is illustrated with data from dementia screening test batteries administered as part of two studies designed to evaluate a wide range of biomarkers throughout the process of normal aging to dementia or Alzheimer's disease.